Electrical stimulation of cardiac adipose tissue‐derived progenitor cells modulates cell phenotype and genetic machinery. (19th February 2013) - Llucià‐Valldeperas, A.; Sanchez, B.; Soler‐Botija, C.; Gálvez‐Montón, C.; Prat‐Vidal, C.; Roura, S.; Rosell‐Ferrer, J.; Bragos, R.; Bayes‐Genis, A.
Abstract: A major challenge of cardiac tissue engineering is directing cells to establish the physiological structure and function of the myocardium being replaced. Our aim was to examine the effect of electrical stimulation on the cardiodifferentiation potential of cardiac adipose tissue‐derived progenitor cells (cardiac ATDPCs). Three different electrical stimulation protocols were tested; the selected protocol consisted of 2 ms monophasic square‐wave pulses of 50 mV/cm at 1 Hz over 14 days. Cardiac and subcutaneous ATDPCs were grown on biocompatible patterned surfaces. Cardiomyogenic differentiation was examined by real‐time PCR and immunocytofluorescence. In cardiac ATDPCs, MEF2A and GATA‐4 were significantly upregulated at day 14 after stimulation, while subcutaneous ATDPCs only exhibited increased Cx43 expression. In response to electrical stimulation, cardiac ATDPCs elongated, and both cardiac and subcutaneous ATDPCs became aligned following the linear surface pattern of the construct. Cardiac ATDPC length increased by 11.3%, while subcutaneous ATDPC length diminished by 11.2% ( p = 0.013 and p = 0.030 vs unstimulated controls, respectively). Compared to controls, electrostimulated cells became aligned better to the patterned surfaces when the pattern was perpendicular to the electric field (89.71 ± 28.47º for cardiac ATDPCs and 92.15 ± 15.21º for subcutaneous ATDPCs). Electrical stimulation of cardiac ATDPCs caused changes in cell phenotype and genetic machinery, making them more suitable for cardiac regeneration approaches. Thus, it seems advisable to use electrical cell training before delivery as a cell suspension or within engineered tissue. Copyright © 2013 John Wiley & Sons, Ltd.